STUDI KORELASI ANTARA PENGETAHUAN MANAJEMEN PERUBAHAN, MOTIVASI CITRA DIRI DAN IKLIM KERJA DENGAN EFEKTIVITAS KERJA STAF SEKRETARIAT RUMAH SAKIT PEMERINTAH - ISTIYANI, ISTIYANI (JURNAL ILMIAH EDUCATIONAL MANAGEMENT, 2011)
The objective of this research is to find out the relationships between change management knowledge, self image motivation and the working climate with the work effectivity of the secretariat staff of public hospital in Jakarta. The method used was the survay with random sampling of 92 respondents from 5 hospitals. The results showed that there is a positive and significant correlation between the change management knowledge, self image motivation and the working climate with the work effectivity of the staff of public hospital. Also a significant and positive correlations were found between those 3 factors and the work effectivity. The results suggest that the mentioned factors should be considered in impovement of the work effectivity.Keywords: Work effectivity, public hospital, change management, selfimage motivation, work climate.